Cross-cultural Transmission of Traditional Chinese Culture via Short Video: Taking Grandpa Aki’s Short Video Series on YouTube as an Example - Xu, Yeqing (European Scientific Journal, ESJ, 2024)
With the development of digitization and online platforms, short videos have become one of the ways to spread traditional Chinese culture. The success of Grandpa Aki’s short videos is a model of cross-cultural transmission of traditional Chinese culture, especially craftsmanship, via short videos. However, few scholars have talked about the implications of cross-cultural transmission of Chinese excellent traditional culture brought by Grandpa Aki’s short video series. The paper analyses the implication of cross-cultural transmission of traditional Chinese culture from the success of Grandpa Aki’s short video series by clarifying the characteristics of these videos and the reasons for the success of these videos.